The Photoelectric Properties of Intrinsic Oxide - p-In4Se3 Heterojunctions - V.N. Katerynchuk; Z.D. Kovalyuk; B.V. Kushnir; O.S. Litvin (Журнал нано- та електронної фізики)
The intrinsic oxide - p-In4Se3 heterojunction was fabricated by the method of thermal oxidation of semiconductor substrate for the first time. The qualitative energy band diagram was built on the basis of analysis of electrical and photovoltaic characteristics of the heterojunction. The character of dominating current transport mechanisms through the barrier is determined by thermionic emission, rather than carrier diffusion. The AFM-images of oxide layer surface and the photosensitivity spectrum of intrinsic oxide  p-In4Se3 heterojunctions also were presented.